Effectiveness of Prompts in Developing the Skill of Answering Questions in Children with Autism Spectrum Disorder - Pervushina O.N; Trubitsyna A.N; Kondratyeva N.G; Pliskovskaya E.N (Moscow State University of Psychology and Education, 2016)
Intraverbal operant (i.e. intraverbal behavior) in B.F. Skinner's concept is a class of verbal reactions that includes understanding what is read, holding conversations and answering questions, and also thoughts and memories. Intraverbals are the foundation for learning simple communications, developing academic skills and acquiring professional ones. Many persons with autism spectrum disorder experience considerable difficulties with intraverbal behavior, and there still is no technique that could teach them how to use it fully and functionally. This research on the effectiveness of various types of prompts in educational trainings was aimed at optimizing teaching intraverbal behavior to children with ASD. The study analyzed how children develop the skill of answering questions in the context of textual and echoic prompts. The experiment with two subjects, children of different sexes aged 8 and 17 years diagnosed with ASD, revealed that textual prompts were more effective. The difference in the effectiveness between textual and echoic prompts proved to be more significant for questions with several or many correct answers than in the case with simple questions having only one correct answer.